In vivo biostability of polysiloxane polyether polyurethanes: Resistance to metal ion oxidation - Ward, Bob; Anderson, James; Ebert, Mike; McVenes, Rick; Stokes, Ken (Journal of biomedical materials research. Part A, 2006)
Polyether polyurethanes are subject to oxidation catalyzed by and through direct (redox) reaction with transition metal ions (cobalt), released by corrosion of metallic parts in an implanted device. Replacing part of the polyether with polysiloxane appears to reduce susceptibility to metal ion oxidation (MIO). In vitro studies indicated that polyurethanes containing 20–35% polysiloxane (PS‐20 and PS‐35) are about optimum. We implanted tubing samples containing cobalt mandrels in the subcutis of rabbits for periods up to 2 years. After 2 years, only traces of microscopic cracks were seen on half the PS‐35 samples, PS‐20 significantly delayed MIO, while the polysiloxane‐free control was very severely degraded. Infrared spectroscopy established that polyether soft segment oxidation was occurring in PS‐20. We could not directly evaluate oxidation in PS‐35 because siloxane bands mask the aliphatic ether. Indirect FTIR evidence suggests that there is very slight polyether oxidation that develops early, and then seems to stabilize. The molecular weight of degraded PS‐20 decreased. That of microcracked PS‐35 decreased negligibly while that of undamaged PS‐35 increased slightly after 2‐year in vivo. The polysiloxane‐free control was profoundly degraded. PS‐20 has much improved MIO resistance, while that for PS‐35 is highly MIO resistant compared with its polysiloxane‐free control. © 2006 Wiley Periodicals, Inc. J Biomed Mater Res, 2006